Influence of retinoic acid on human gingival epithelial barriers. (1st February 2016) - Groeger, S.; Jarzina, F.; Windhorst, A.; Meyle, J.
Abstract : Background and Objectives: The gingival epithelium plays an important role in the protection of oral tissues from microbial challenge. Oral keratinocytes form a barrier and show various cellular contacts, including tight junctions (TJ). To analyse the barrier function in vitro the transepithelial electrical resistance (TER) is commonly used. Retinoic acid (RA) is an important signalling molecule in most tissues, including epithelial differentiation. RA signalling is mediated through three RA receptors. The aim of the study was to investigate the influence of RA on human gingival barriers in vitro . Material and Methods: Immortalized human gingival keratinocytes were seeded on culture plate inserts. The effect of RA with and without infection with Porphyromonas gingivalis W83 on the barrier was analysed by TER measurements. The expression of TJ proteins was investigated by western blot. Results: During differentiation, mean TER increased from 16 (1 h), 43 (4 h) to 62 (6 h) Ohm × cm 2 . Addition of 15 μm RA increased TER by +19 after 1 h, +25 after 4 h and +16 Ohm × cm 2 after 6 h. The pan‐RA receptor inhibitor BMS 493 resulted in TER values comparable to the control. The mean established TER of the control was approximately 110 Ohm × cm 2 . Addition of 15 μm RA elevated TER to 127 Ohm × cm 2 after 1 h, 150 Ohm × cm 2 after 4 h and 189 Ohm × cm 2 after 6 h ( p ≤ 0.01). RA plus infection with P. gingivalis W83 further increased the TER increasing effect but could not prevent the destruction of TER induced by bacterial infection. The protein expression of the TJ proteins claudin 4 and occludin was enhanced while ZO‐1 was downregulated after 1 h of RA incubation. Conclusion: RA provides barrier‐positive elements to the gingival epithelial cell model that is accompanied by altered expression of TJ proteins.